Constraining the Origins of the Magnetism of Lepidocrocite (γ-FeOOH): A Mössbauer and Magnetization Study - Guyodo, Yohan; Bonville, Pierre; Till, Jessica L.; Ona-Nguema, Georges; Lagroix, France; Menguy, Nicolas (Frontiers in Earth Science, 2016)
Lepidocrocite, a widespread environmentally relevant iron oxyhydroxide, has been investigated for decades using 57Fe Mössbauer spectroscopy and magnetic measurements. However, a coherent and comprehensive interpretation of all the data is still lacking due to seemingly contradictory interpretations. On one hand, temperature dependence of magnetic susceptibility and Mössbauer spectra resemble those of superparamagnetic nanoparticles with diameters less than 10 nm even though physically particles are lath-shaped with lengths on the order of 100-300 nm. On the other hand, in-field Mössbauer spectra show that lepidocrocite is an antiferromagnet and becomes paramagnetic above 50-70 K, a temperature close to the blocking temperature deduced from susceptibility data. The present study investigates a well-characterized synthetic sample of lepidocrocite, includes modelling of Mössbauer spectra and dc and ac magnetization data, and proposes a solution to this paradox. The new data are coherent with the presence of two entities in lepidocrocite: a bulk antiferromagnetic matrix and sparse ferrimagnetic nanosized inclusions (d = 3.4 nm), akin to maghemite, embedded within. The presence of nanosized ferrimagnetic inclusions is confirmed for the first time by Mössbauer spectroscopy.